Domoic Acid - C. Cortinovis; L. J. Spicer; M. C. Perego; T. Coccini; F. Caloni (CRC Press, 2019)
In the summer of 1961, thousands of sooty shearwaters (Puffinus griseus), a medium-large long-winged seabird that feeds on krill, squid, and fish, converged on the shores of North Monterey Bay, California. The birds were found regurgitating anchovies, crashing through glass windows, attacking people, shrieking vocalization uncommon for this species, and dying on the streets. 1 This episode inspired Hitchcock's 1963 horror film “The Birds” and has been later linked to domoic acid (DA) poisoning. 2 Since then episodes of disorientation, stereotypic scratching, seizures, and death associated with DA toxicity have been reported in California sea lions (Zalophus californianus), brown pelicans (Pelecanus occidentalis), Brant's cormorants (Phalacrocorax penicillatus), pygmy sperm whales (Kogia breviceps), dwarf sperm whales (Kogia sima), minke whales (Balaenoptera acutorostrata), and northern fur seals (Callorhinus ursinus). 3–10 The first documented episode of DA poisoning in humans occurred in Canada in 1987 when over 100 people developed gastrointestinal (vomiting, abdominal cramps, and diarrhoea) and/or neurological signs (headache, short-term memory loss, disorientation, and, in severe cases, seizures and coma) as well as fatalities after ingesting contaminated mussels (Mytilus edulis). 11 Because of the short-term memory loss observed in many of the affected patients, the condition was subsequently termed amnesic shellfish poisoning (ASP). This chapter reviews the chemical characteristics, occurrence, toxicokinetics, and mechanism of action of DA as well as the epidemiological data, clinical features, diagnosis, treatment, and prevention of ASP.